Direct thin smear as an alternative to kato thick smear and wet mount preparation in the diagnosis of human parasitic intestinal helminth infection - Rayel, Renato Jr. D.
A new rapid thin-preparation high-value direct smear with simultaneous disinfection and fixation process based on Papanicolau smear was developed as stool examination method. A total of 51 stool samples were collected from high-risk populations in Davao City, Philippines and examined using the new method and two commonly used techniques, namely Direct Fecal Smear and Kato Thick Smear. Ascaris lumbricoides, Trichuris trichiura, hookworm and heterophyes were identified and the three methods were compared based on their sensitivity, negative predictive value and diagnostic accuracy in detecting parasitic infection. The technique was found to have higher ratings than Direct Fecal Smear and equal or comparable ratings to Kato Thick Smear for trichuris trichiura, bookworm and Heterohpjyes heterophyes. Direct Thin Smear sensitivity ratings for Trichuris, bookworm and Heterophyes, respectively, were 96.30%, 90.91% and 100% compared to Kato Thick Smear ratings of 100%, 90.91%, and 100% and Direct Fecal Smear ratings of 55.56%, 18.18% and 0.00%. It was also found to have comparable ratings to Direct Fecal Smear which was the turned out to have the highest sensitivity for Ascaris lumbricoides and equal ratings to Kato Thick Smear. Direct Thin Smear index of agreement with Direct Fecal Smear and Kato Thick Smear, respectively, were -.8115 an 0.9015 or excellent agreement in both cases
Thesis (BS Biology) -- University of the Philippines Mindanao, 2007
Keywords: Kato Thick Smear; Human parasitic intestinal helminth infection